Kedudukan Walimatul â€˜Urs Dalam Masyarakat Aneuk Jamee Dari Perspektif MaqÄá¹£id SyariÊ½ah - Cut Putri Yulyana Mahendra; Jabbar Sabil; Azka Amalia Jihad (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2021)
Walimatul'urs is a recommendation in Islam. Walimatul 'urs aims as syi'ar and becomes a sunnah muakadah. In the Aneuk Jamee community, the traditional walimah has several series of customs running for seven days, thus many costs must be incurred during the implementation of this waimah. So that many people who have walimah choose to go into debt when they are going to have walimah. Walimah is considered important and has its own position for the Aneuk Jamee community. With this assumption, it is not uncommon to find that they are willing to borrow for the sake of carrying out walimah. In this study, the main problem in this study is how the practice of walimah 'urs in the aneuk jamee community and how the practice of walimatul 'urs in the aneuk jamee community from the perspective of maqÄá¹£id shariah. The data obtained by the authors were obtained from observations and interviews with the community and related traditional leaders. From the results of the research, many of the Aneuk Jamee community carry out walimah beyond their ability, with the seven-day traditional series that costs a lot so that debt is the best way for the implementation of walimah. Walimatul 'urs in the perspective of maqÄá¹£id shari'ah, if it is difficult then it is not in accordance with maqÄid shari'ah because in the context of maintaining the inheritance of marriage it should not be forced so that debt can cause harm to debtors whose purpose is to maintain existence in the community so that it causes redundancy.